Surveillance and control of asymptomatic carriers of drug-resistant bacteria - Jamrozik, Euzebiusz (Bioethics, 2019)
Drug-resistant bacterial infections constitute a major threat to global public health. Several key bacteria that are becoming increasingly resistant are among those that are ubiquitously carried by human beings and usually cause no symptoms (i.e. individuals are asymptomatic carriers) until and/or unless a precipitating event leads to symptomatic infection (and thus disease). Carriers of drug-resistant bacteria can also transmit resistant pathogens to others, thus putting the latter at risk of resistant infections. Accumulating evidence suggests that such transmission occurs not only in hospital settings but also in the general community, although considerably more data are needed to assess the extent of this problem. Asymptomatic carriage of drug-resistant bacteria raises important ethical questions regarding the appropriate public health response, including the degree to which it would be justified to impose burdens on asymptomatic carriers (and others) in order to prevent transmission. In this paper, we (i) summarize current evidence regarding the carriage of key drug-resistant bacteria, noting important knowledge gaps; and (ii) explore the particular implications of existing public health ethics frameworks for policy-making regarding asymptomatic carriers. Inter alia, we argue that the relative burdens imposed by public health measures on healthy carriers (as opposed to sick individuals) warrant careful consideration and should be proportionate to the expected public health benefits in terms of risks averted. We conclude that more surveillance and research regarding community transmission will be needed in order to clarify relevant risks and design proportionate policies, although extensive community surveillance itself would also require careful ethical consideration.